The Monetary Value of Market Replaceable Household Production: An Empirical Study of the Economic Significance of Housewives’ Roles - Mulyaningsih, Tri; Purwaningsih, Yunastiti; Anggun, Kurnia (Makara Human Behavior Studies in Asia, 2018)
Abstract: Economic theory in the household production literature suggests that the division of labor within households is based on the comparative advantage of specific investments and intrinsic biological differences between males and females. Males are typically regarded as breadwinners, whereas females are believed to be responsible for raising children and performing domestic work. Moreover, domestic tasks performed by housewives are not accorded enough economic significance; these tasks are also not included in the calculation of Gross Domestic Product and Gross NationalProduct. This study aims to estimate the monetary value of the domestic tasks performed by housewives in urban Surakarta, Central Java, Indonesia. To this end, this study employs the general replacement cost approach. A primary survey of 385 respondents was conducted to collect information from housewives in Surakarta. The purposive sampling technique was used to generate are presentative sample covering all five districts of Surakarta. The findings show that the average monthly monetary value of housewives in Surakarta is close to 2.5 million Rupiah. The monetary value varies according to the following parameters: age group, educational qualifications, age of children, and housewives’ roles—that is, those who perform only domestic work and those who take up jobs in the public sphere in addition to performing domestic work.